Gradient Silica Loading: Performance Analysis of PEMFCs Under Temperature-Humidity Variations - Qiang Bai; Chuangyu Hsieh; Zhenghong Liu; Qipeng Chen; Fangbor Weng (Batteries)
Fuel cells, as one of the most promising alternatives to lithium-ion batteries for portable power systems, still face significant challenges. A critical issue is their substantial performance degradation under low-humidity conditions. To address this, researchers commonly add silica to components. This study employs a control variable method to systematically investigate the impact of four parameters—gas stoichiometry, temperature, humidity, and silica content—on fuel cell performance. Initially, the effects of gas stoichiometry, temperature, and humidity on performance were examined. Subsequently, hydrophilic silica was incorporated into the membrane electrode assembly (MEA) to assess its potential for improving performance in low-humidity environments. Experimental results reveal that under 100% humidification, silica addition had a minimal impact on performance, particularly at high temperatures where performance improved by only 2.5%. This is attributed to increased water production at elevated temperatures, which—when combined with silica’s water retention properties—exacerbates flooding. However, when humidity was reduced to 50%, silica incorporation significantly enhanced performance. At high temperatures, silica addition resulted in a 126.2% performance improvement, demonstrating its efficacy as a rational strategy under low-humidity conditions.